2022
DOI: 10.3390/vaccines10030463
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Vaccine-Preventable Diseases in Four Districts of Xaysomboun Province, Lao People’s Democratic Republic

Siriphone Virachith,
Mapor Lao,
Magnoula Inthepphavong
et al.

Abstract: Xaysomboun province has some of the lowest health indicators in Lao People’s Democratic Republic (PDR). This cross-sectional study aimed to determine the vaccination, susceptibility and exposure status of the population to hepatitis B virus (HBV), measles, rubella, and tetanus. Participants aged 5 years and older were randomly selected from four districts. From each enrolled participant, demographic data and 5 mL of blood sample were taken. HBV surface antigen (HBsAg) and antibodies against HBV, measles, rubel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…However, the IgG prevalence against measles and rubella in the age group of 1-2 years is still in the lower range of the herd immunity threshold. Other seroprevalence studies conducted in several provinces in Lao PDR have also found a low prevalence of measles antibodies among infants and young age groups, given routine and SIA vaccination services [26][27][28][29] . This might indicate heterogeneity in the measles vaccination among provinces or between rural versus urban areas.…”
Section: Discussionmentioning
confidence: 87%
“…However, the IgG prevalence against measles and rubella in the age group of 1-2 years is still in the lower range of the herd immunity threshold. Other seroprevalence studies conducted in several provinces in Lao PDR have also found a low prevalence of measles antibodies among infants and young age groups, given routine and SIA vaccination services [26][27][28][29] . This might indicate heterogeneity in the measles vaccination among provinces or between rural versus urban areas.…”
Section: Discussionmentioning
confidence: 87%
“…Lao People’s Democratic Republic (PDR), which is located in Southeast Asia and has a population of approximately 7 million people, exhibits a high morbidity and mortality due to HBV infection. Vaccination was introduced in 2001 and combined diphtheria, tetanus, pertussis, hepatitis B and Haemophilus influenzae vaccine is currently scheduled at 6, 10 and 14 weeks of age 8. Since 2003, birth-dose vaccination is recommended in addition 9.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination was introduced in 2001 and combined diphtheria, tetanus, pertussis, hepatitis B and Haemophilus influenzae vaccine is currently scheduled at 6, 10 and 14 weeks of age. 8 Since 2003, birth-dose vaccination is recommended in addition. 9 Maternal HBV screening (by HBsAg rapid test) is also recommended, but is unevenly implemented in the country.…”
Section: Introductionmentioning
confidence: 99%